Tests of factorial structure and measurement invariance for the Student Engagement Instrument: Evidence from middle and high school students in Portugal - Moreira, Paulo (2018)
Corresponding Author: Paulo Moreira, Centro de Investigação em Psicologia para o Desenvolvimento (CIPD), Universidade Lusíada - Porto, Rua Dr. Lopo de Carvalho, 4369-006,Porto, Portugal, email: paulomoreira@por.ulusiada.pt